Training Teachers at a Distance - Perraton, Hilary; Commonwealth Secretariat, London (England). (Washington, D.C. : Distributed by ERIC Clearinghouse, 1984)
This handbook discusses the use of distance education for teacher training and examines the case for and against distance teaching; its organization; the development, production, and distribution of distance-teaching materials; tutoring and counseling; and the monitoring and evaluation of finance and resources. Distance teaching is defined as the use of correspondence courses with radio and some face-to-face study. Alternative models for the administration of distance teaching are compared, and administrative functions are distinguished. The development of teaching materials through print or radio and planning for their production and distribution are examined. In discussing tutoring and counseling, distinctions are made between the functions of school and college staff, correspondence and radio tutors, and student advisers. Both the evaluation of the progress of individual students and formative assessment of a program are analyzed. Budgeting is discussed, and the factors affecting costs are compared with those of conventional education. Appendices include a 21-item bibliography and notes on the characteristics of educational media and language testing. (Author/LMM)
Availability: Commonwealth Secretariat, Marlborough House, Pall Mall, London SW1Y 5HX (3 British pounds).
Policymakers.
Practitioners.
Microfiche.
Keywords: Administration; Budgeting; Correspondence Study; Costs; Distance Education; Educational Radio; Foreign Countries; Material Development; Models; Program Development; Program Evaluation; Teacher Education; Tutoring; Guides, Non-Classroom.; Information Analyses; Reports, Descriptive